P4_12 Mirror, Mirror - Davis, Claire; Tilley, Freddie; Hague, Pete (Physics Special Topics, 2011)
The existence of mirror matter is explored as a possible solution to the lack of conservation of parity in particle interactions. Ways in which this matter would present itself in the universe are discussed, as are possible methods for observing it in order to confirm or deny its existence. It is found that it is possible for mirror matter to be indirectly observed, but not necessarily recognised.